Penny Penguin [compact disc] - Raffi (Craft Recordings, 2024)
Penny Penguin is the 26th studio album from legendary children's musician and global troubadour Raffi. A collaboration with Canadian Juno Award-winning folk/country trio Good Lovelies, the album brings together 14 child-friendly tracks that every Raffi fan and young child will love to sing and dance along with.